Avaliação da qualidade da ultrassonografia tridimensional mediante as técnicas Fast, Star e Five D-Heart no rastreamento das doenças cardíacas congênitas - Carrilho, Milene Carvalho [UNIFESP] (2020)
Objective: To compare the quality of standard fetal echocardiographic views obtained by three-dimensional ultrasound with those obtained by the simple targeted arterial rendering (STAR) technique, four-chamber view swing technique (FAST), and fetal intelligent navigation echocardiography (FINE / 5D-Heart®) technique. Methods: This was a cross-sectional prospective study that included pregnant women between 22 and 34 weeks of gestation, with normal fetuses. Fetal heart volumes were acquired using spatio-temporal image correlation (STIC) with the fetal spine between 2 and 9 o’clock. The FAST/STAR techniques consist of the manipulation of STIC volumes by drawing OmniView® lines to obtain echocardiographic views. The FINE technique uses intelligent navigation to automatically generate echocardiographic views. The quality of the images was classified as excellent, good, acceptable, and unacceptable. The analysis was performed using the Bonferroni multiple-comparisons test. Results: The study included 101 pregnant women aged between 16 and 44 years (mean ± standard deviation of 32 ± 6.3) at a gestational age of 20 to 34 weeks (mean ± standard deviation of 26 ± 4.2). There was no mean difference in image quality between fetal spine positions in all views (p>0.05). However, in the five-chamber, left ventricular outflow tract, right ventricular outflow tract, ductal arch, superior vena cava/inferior vena cava, and abdomen/stomach views, there was a statistically significant mean difference between the techniques of reconstruction of the standard echocardiographic views, regardless of the spine position (p<0.05). The best mean image quality was obtained by the FINE technique. Conclusion: The quality of the echocardiographic views obtained using the FINE/5D-Heart® technique was superior to that of those generated by the FAST/STAR techniques in normal fetuses scanned between 20 and 34 weeks of gestation.